Selection of number of neurons for vector quantization methods - Kurasova, Olga; Molytė, Alma (Lietuvos matematikos rinkinys, 2008)
In this paper, a strategy of the selection of the neurons number for vector quantization methods has been investigated. Two methods based on neural networks have been analysed: self-organizing map and neural gas. There is suggested a way under which the number of neurons is selected taken into account the particularity of the analysed data set.